Introducing greenswales: a nature-based approach to preserve seasonal channels – Learnings from Chandigarh, India - Sood, Ankita; Biswas, Arindam (Geographica Pannonica, 2022)
For long, the cities depended on grey infrastructure for draining stormwater. However, incidences of pluvial flooding are increasing, and existing grey infrastructure is unable to take up the additional stormwater load. Consequently, planners are forced to think of new and sustainable alternatives for stormwater management. Natural channels can supplement the stormwater drainage systems, but these channels in cities are reclaimed to provide land for housing and other functions despite their crucial role. This study presents the case of a natural channel in Chandigarh (India) that is redeveloped as a greenspace without compromising its function of stormwater conveyance. We analytically discussed the non-intentional preservation of this seasonal natural channel and introduced a new term, greenswales, for similar arrangements. A greenswale is defined as the stretch of greenspaces laid over a natural channel, ephemeral or intermittent, having stormwater detention and conveyance as primary functions during precipitation. This study's significant finding is that the seasonal natural channels in a city can be safeguarded through the judicious superimposition of green spaces over them. Crucial lessons from this case can guide new developments in utilising natural seasonal channels as a nature-based solution for stormwater management, reducing the load on grey infrastructure and providing the city with a greenspace.
Keywords: greenswales; pluvial flooding; natural channels; nature-based solutions; urban streams; stormwater management